Learning Difficulties in Islamic Religious Education Among Elementary School Students: Experiences, Impacts, and Teacher Support - Ratih Novianti; Zuhdiyah Zuhdiyah; Karoma Karoma; Indah Wigati; Maryamah Maryamah (AL-ISHLAH: Jurnal Pendidikan, 2026)
Learning difficulties in Islamic Religious Education can restrict students’ access to Arabic-script materials, reduce classroom participation, and affect their confidence. This study aimed to examine the forms, perceived contributing factors, and consequences of these difficulties, as well as the instructional support provided by teachers. A qualitative descriptive design was employed involving 22 participants from 11 public elementary schools in Kemuning District, Palembang, Indonesia: 11 fifth-grade students experiencing persistent difficulties in Islamic Religious Education and 11 certified teachers. Data were collected through semi-structured interviews, teacher learning notes, student reflections, and relevant academic documents, and were analyzed using Braun and Clarke’s six-phase thematic analysis. Five themes were identified: Arabic literacy as a gateway barrier, mismatch between students’ processing pace and classroom demands, emotional and social consequences of repeated difficulty, limited support outside school, and adaptive teacher support. Students reported difficulties recognizing and writing Hijaiyah letters, retaining memorized material, completing tasks at the expected pace, and participating confidently in class. Teachers responded through individualized guidance, chunking, slower instructional pacing, auditory and narrative supports, repetition, and positive reinforcement, which participants perceived as helpful. The findings indicate that learning difficulties in Islamic Religious Education are shaped by the interaction of linguistic, cognitive, emotional, instructional, and environmental conditions. Inclusive practice therefore requires gradual instructional sequencing, emotionally safe classrooms, and stronger collaboration between schools and families.